2020
DOI: 10.1016/j.physletb.2019.135030
|View full text |Cite
|
Sign up to set email alerts
|

Configurational entropy and instability of tachyonic braneworld

Abstract: We consider tachyonic braneworld with a bulk cosmological constant and investigate a configurational entropy of various magnitudes of scale factor. It is found that for a bulk negative/zero cosmological constant, the configurational entropy has a global minimum when the magnitude of scale factor reaches the critical value. This result seems to have intriguing implications such that an accelerated rate of the universe and cosmological inflation rate for radiation/matter domination are able to be determined by s… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(1 citation statement)
references
References 42 publications
0
1
0
Order By: Relevance
“…The CE has suggested that the informational content in physical systems with localized energy density configurations through measure of their ordering in field configuration space [12,13]. It has been extensively investigated for AdS/QCD holographic models [14][15][16][17][18][19][20][21][22][23][24] and performed for a detailed analysis of the thermal stability of a variety of physical systems [13][14][15][20][21][22][23][24][25][26][27][28][29][30][31][32][33][34][35][36]. Thus, it is intriguing that the issue of the stability is generalized to the accelerating BH with the negative cosmological constant in four-dimensional spacetime.…”
Section: Introductionmentioning
confidence: 99%
“…The CE has suggested that the informational content in physical systems with localized energy density configurations through measure of their ordering in field configuration space [12,13]. It has been extensively investigated for AdS/QCD holographic models [14][15][16][17][18][19][20][21][22][23][24] and performed for a detailed analysis of the thermal stability of a variety of physical systems [13][14][15][20][21][22][23][24][25][26][27][28][29][30][31][32][33][34][35][36]. Thus, it is intriguing that the issue of the stability is generalized to the accelerating BH with the negative cosmological constant in four-dimensional spacetime.…”
Section: Introductionmentioning
confidence: 99%